Effects of some heavy metals on in vitro pollen germination and tube growth of apricot (Armenica vulgaris Lam.) and cherry (Cerasus avium L.) - Gür, Nazmi; Topdemir, Aykut (My University, 2008)
The aim of the study was to determine the influence of heavy metals (Cd, Cu, Hg and Pb) on the pollen germination and tube growth of Apricot and Cherry. This study demonstrated heavy metals led to a significant decrease pollen germination and tube growth of apricot and cherry. There was a reduction in pollen germination and tube elongation as metal concentrations increased. Cu had the highest toxic effect on pollen of apricot while Pb had the least effect. Cherry pollen germination and tube growth was mostly inhibited by Hg and Cd, but only weakly by Pb.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Pollen germination; Apricot; Cherry; Heavy metals